Analisis dan Rencana Pengelolaan Sampah di Perguruan Tinggi Sesuai Konsep Green Campus (Studi Kasus: Universitas Respati Yogyakarta) - Pascawati, Nur Alvira; Lustiyati, Elisabeth Deta; Untari, Jati; Ramadanti, Dea Putri (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
The expansion and growth of Higher Education in Indonesia are very rapid with a large population, large area, and dense activity, resulting in significant waste generation. This is a very big challenge to achieve sustainable development if there is no systematic, comprehensive, and sustainable waste management. This study was to analyze and plan waste management according to the green campus concept. This research uses a descriptive-quantitative method with a case study strategy at Universitas Respati Yogyakarta. The population and sample are all waste generated in the campus area and all documents related to the waste recycling program. The research instrument uses 2 guidelines: measurement of waste generation and composition refers to the SNI and waste management analysis based on guidelines from UI GreenMetric. The results showed that the generation (0.021kg/person/day) and volume of waste (0.369/kg/person/day) were above the SNI values and most types of waste are inorganic. The waste containers provided do not meet SNI: volume, number, color, and several waste collection tools. The campus has a program to reduce the use of paper and plastic, but it has not been maximized because there is no recycling program, >75% of organic waste has not been handled, there is no handling of B3 waste and the method of disposing of liquid waste is still conventional. The conclusion is that the campus waste management system gets a poor score on the Green Campus. Handling waste on site is a step that must be carried out before being disposed of in a container.